Liberdade e bens primários: uma investigação da teoria de John Rawls a partir do liberalismo clássico - Mendes, Lucas (2009)
The purpose of this dissertation is to analyze the concepts of basic liberties and primary goods in John Rawls theory of justice. The investigation is based on Rawls A Theory of Justice and Political Liberalism (in addition to other books and articles by the same author), and attempts to ascertain how closely Rawls liberalism approximates to classical liberalism. To this end, the analysis is divided into four stages. First of all, a general overview of Rawls theory of justice as equity is given. Secondly, the ideas of classical liberalism are expounded. Thirdly, the concept of basic liberties in Rawlsian theory is set out and, with this in mind, the starting point is Rawls Theory of Justice, followed by the critiques of Hart, Rothbard and Shapiro, and ending with Rawls replies to these critiques. Fourthly, the concept of primary goods is presented, and follows the same line of explanation as for basic liberties. In this chapter, the critiques of Arrow, Sen and Kymlicka are examined. In the conclusion to the dissertation, the distinctions and similarities between Rawlsian liberalism and classical liberalism are outlined in the light of an analysis of basic liberties and primary goods.